Feature Extraction Techniques for Leukocyte Classification - A Review - Baby, Diana; Juliet Devaraj, Sujitha (International Journal of Engineering and Technology, 2018)
This paper covers an investigation on the various feature extraction techniques employed for the statistical estimation of leukocyte classification from blood sample images since the identification or analysis of these four classes of leukocytes plays a vital role in the early identification of various diseases. The manual estimation of these WBCâ€™s by pathologist is error prone and time consuming. This paper mainly concentrates on the study of leukocyte classification methodology and various feature extraction techniques for the classification of four classes of Leukocytes such as Neutrophil, Lymphocyte, Monocyte, and Eosinophil which can be fed to SVM or neural network for further classification.Â